Anti–amyloid β autoantibodies in cerebral amyloid angiopathy–related inflammation: Implications for amyloid‐modifying therapies. Issue 4 (26th April 2013) - Piazza, Fabrizio; Greenberg, Steven M.; Savoiardo, Mario; Gardinetti, Margherita; Chiapparini, Luisa; Raicher, Irina; Nitrini, Ricardo; Sakaguchi, Hideya; Brioschi, Monica; Billo, Giuseppe; Colombo, Antonio; Lanzani, Francesca; et al.
<x xml:space="preserve">Abstract</x> Objective Cerebral amyloid angiopathy–related inflammation (CAA‐ri) is characterized by vasogenic edema and multiple cortical/subcortical microbleeds, sharing several aspects with the recently defined amyloid‐related imaging abnormalities (ARIA) reported in Alzheimer's disease (AD) passive immunization therapies. Herein, we investigated the role of anti–amyloid β (Aβ) autoantibodies in the acute and remission phases of CAA‐ri. Methods We used a novel ultrasensitive technique on patients from a retrospective multicenter case–control study, and evaluated the anti‐Aβ autoantibody concentration in the cerebrospinal fluid (CSF) of 10 CAA‐ri, 8 CAA, 14 multiple sclerosis, and 25 control subjects. Levels of soluble Aβ40, Aβ42, tau, P‐181 tau, and APOE genotype were also investigated. Results During the acute phase of CAA‐ri, anti‐Aβ autoantibodies were specifically increased and directly correlated with Aβ mobilization, together with augmented tau and P‐181 tau. Following clinical and radiological remission, autoantibodies progressively returned to control levels, and both soluble Aβ and axonal degeneration markers decreased in parallel. Interpretation Our data support the hypothesis that the pathogenesis of CAA‐ri may be mediated by a selective autoimmune reaction against cerebrovascular Aβ, directly related to autoantibody concentration and soluble Aβ. The CSF dosage of anti‐Aβ autoantibodies with the technique here described can thus be proposed as a valid alternative tool for the diagnosis of CAA‐ri. Moreover, given the similarities between ARIA developing spontaneously and those observed during immunization trials, anti‐Aβ autoantibodies can be considered as novel potential biomarkers in future amyloid‐modifying therapies for the treatment of AD and CAA. Ann Neurol 2013;73:449–458